IMPLEMENTATION OF OAUTH 2.0 BASED ON LARAVEL FRAMEWORK IN A CASE STUDY OF CLIENT INFORMATION MANAGEMENT SYSTEM - Arthur Oliviana Zabka; Asep Id Hadiana; Herdi Ashaury (Journal of Informatics and Communication Technology (JICT), 2023)
The swift growth of the internet and its utilization by businesses for operational purposes, such as developing information systems and utilizing cloud-based data storage, has been remarkable. The discussed client data recording system is designed to facilitate the recording of wedding photography bookings, easing the workload for employees. However, the rapid expansion of the internet has also introduced security concerns, particularly regarding unauthorized access due to weak website authorization and authentication. Consequently, ensuring and effectively managing access rights to information systems becomes crucial. This study aims to implement secure website login authorization using the OAuth 2.0 method with Laravel Passport in the client data recording information system. Post-authentication, the authorization in the context of OAuth2, used within Laravel Passport, provides users with access tokens to reach the primary interface. This process involves an API that both furnishes and safeguards the intended resources. Upon authentication and receipt of a valid access token from the OAuth2 system, users can utilize the token to access the API. The research outcomes enhance the security of information system access rights, aiming to reduce unauthorized breaches in websites storing vital data, thus ensuring the safety and protection of stored client data. Testing results using SQL Injection yielded 4418 messages sent and 2209 task IDs, with a current fuzzer count of 0, signifying that the system remained secure and impervious to SQL Injection attacks.